2009
DOI: 10.1103/physrevb.80.121403
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved Raman spectroscopy of optical phonons in graphite: Phonon anharmonic coupling and anomalous stiffening

Abstract: Time-resolved Raman spectroscopy has been applied to probe the anharmonic coupling and electron-phonon interaction of optical phonons in graphite. From the decay of the transient anti-Stokes scattering of the G-mode following ultrafast excitation, we measured a lifetime of 2.2 ± 0.1ps for zone-center optical phonons. We also observed a transient stiffening of G-mode phonons, an effect attributed to the reduction of the electron-phonon coupling for high electronic temperatures.Because of its intimate relation w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
178
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(206 citation statements)
references
References 36 publications
28
178
0
Order By: Relevance
“…They concluded that more than 90% of the initially deposited excitation energy is transferred to a few SCOPs immediately after thermalization; the carrier scattering rate increases from 10 THz at equilibrium to 14 THz shortly after photoexcitation resulted from scattering from hot SCOPs. The slow decay of T e with a time constant of 7 ps was interpreted as the SCOP lifetime, which is compatible with the value of 2 ps from a direct measurement based on the time-resolved Raman spectroscopy (Yan et al, 2009).…”
Section: Graphitic Nanostructuresmentioning
confidence: 63%
“…They concluded that more than 90% of the initially deposited excitation energy is transferred to a few SCOPs immediately after thermalization; the carrier scattering rate increases from 10 THz at equilibrium to 14 THz shortly after photoexcitation resulted from scattering from hot SCOPs. The slow decay of T e with a time constant of 7 ps was interpreted as the SCOP lifetime, which is compatible with the value of 2 ps from a direct measurement based on the time-resolved Raman spectroscopy (Yan et al, 2009).…”
Section: Graphitic Nanostructuresmentioning
confidence: 63%
“…The acoustic and optical phonon baths can each establish a different temperature upon interactions with the electrons, but processes such as anharmonic phonon-phonon scattering serve to thermalize them on a picosecond time scale 3,[63][64][65] . In this work, we shall assume a common lattice temperature T L , but acknowledge that in experiments with ultrafast pump-probe, this will not hold true.…”
Section: B Cooling Dynamicsmentioning
confidence: 99%
“…Hence, we expect to measure a delayed rise and a lower peak signal for excitation with x-polarized light compared to excitation with y-polarized light. We also expect the two curves to overlap once the distribution becomes isotropic, before further cooling by optical and acoustic phonon emission occurs at longer time delays [17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%